Why a Narrowly Defined Legal Scholarship Blog Is Not What I Want: An Argument in Pseudo-Blog Form - Ann Althouse (Washington University Law Review, 2006)
Written in the form of a blog, this paper highlights the creative and communicative benefits of blogging, in particular legal blogging. This comment argues that aside from being intrinsically rewarding, blogging offers a concise scholarly model addressing a wider-ranger of topics. In this way, the paper claims that blogging has the potential for self-discovery and innovation in a way that legal scholarship might not.
Keywords: Blogs; Law -- Study & teaching; Pseudonyms; United States